Irradiation doses and evaluation of measures of radiological protection of population dwelling in the most radioactively contaminated territories of Ukraine. - I. M. Khomenko (Medičnì Perspektivi, 2014)
Analysis and evaluation of the most used measures of radiological protection in the country and levels of irradiation of the population dwelling on the most radioactively contaminated territories due to the Chernobyl catastrophe was conducted. The levels of cumulative and committed doses of irradiation were evaluated by the results of their reconstruction. Data of the regional sanitary and epidemiological station on detection of the content of radionuclides in the body were also used. They were detected by means of the radiation meter of a person. Primary information on morbidity was analysed by changes in the dynamics of observation of certain territories. Based on the analysis of the existing national data it was shown that in certain centres of population of Ovruch district of Zhytomyrska oblast irradiation doses in 1986-2013 exceeded the specified by national legislation criterion of the dose of 70 mSv within the life. During this period in population there were realized about 92% from the committed calculated dose of irradiation within the life and irradiation with small closes continues. Only a small part of respondents uses countermeasure to get radioactively non-polluted foodstuffs. The defined peculiarities indicate the necessity to continue taking protective measures from ionizing radiation of the population.